2020
DOI: 10.1016/j.breast.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

A high neutrophil-lymphocyte ratio and platelet-lymphocyte ratio are associated with a worse outcome in inflammatory breast cancer

Abstract: Introduction Inflammatory breast cancer (IBC) is an uncommon, but aggressive form of breast cancer that accounts for a disproportionally high fraction of breast cancer related mortality. The aim of this study was to explore the peripheral immune response and the prognostic value of blood-based biomarkers, such as the neutrophil-to-lymphocyte ratio (NLR), in a large IBC cohort. Patients & methods We retrospectively identified 127 IBC patients and collected lab results fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…NLR is already reported as a predictor of outcomes for malignancy including gastric cancer, lung cancer, breast cancer, colon cancer, etc. [ 19 , 20 , 21 , 22 ]. NLR is also a predictor of surgical outcomes for HCC and low NLR had a better overall survival [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…NLR is already reported as a predictor of outcomes for malignancy including gastric cancer, lung cancer, breast cancer, colon cancer, etc. [ 19 , 20 , 21 , 22 ]. NLR is also a predictor of surgical outcomes for HCC and low NLR had a better overall survival [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Many lines of evidence have demonstrated that cancer patients with systemic inflammation are characterized by inadequate antitumor responses and unfavorable outcomes compared with those patients without systemic inflammation. [4][5][6][7][8][9][10][11][12][13] In addition to systemic inflammation, the nutritional status of cancer patients is another aspect that can affect antitumor treatment efficacy. Several nutritional indexes, such as the prognostic nutritional index (PNI), nutritional risk index (NRI), and controlling nutritional status (CONUT) score, have been closely correlated with treatment-related complications, therapeutic responses, and clinical outcomes in various cancer types, including NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Sections were then dewaxed in xylene, stained in hematoxylin and eosin (H&E), dehydrated, and mounted with a coverslip [ 19 ]. NLR has been widely used as a predictive factor for inflammatory status [ 20 23 ] and analyzed in the present work.…”
Section: Methodsmentioning
confidence: 99%